Anti-human leukocyte antigen-DPB1 antibody-associated transfusion-related acute lung injury after hematopoietic stem cell infusion - Mehmet Can Balkan; Fatma Visal Okur; Fatma Burcu Belen Apak; Sevil Babayeva; Numan Firat Ekici; Baris Kuskonmaz; Duygu Uckan Cetinkaya (Asian Journal of Transfusion Science)
Although relatively rare among transfusion reactions, transfusion-related acute lung injury (TRALI) is a life-threatening condition, making its prevention, recognition, and early intervention extremely important. Although many etiological factors have been identified, the most common reasons are anti-human leukocyte antigen (anti-HLA) and anti-human neutrophil antigen antibodies that pass from the donor to the recipient during transfusion. TRALI was shown with transfusion of all kinds of blood products, however, it is rarely seen after stem cell infusion. Despite an adult case who developed TRALI after stem cell infusion, there is no pediatric case of TRALI associated with hematopoietic stem cell infusion in the previous literature. Here, we report a pediatric case with TRALI after infusion of the hematopoietic stem cell product from his female donor who has recently given birth 6 months ago. A 9-year-old patient with acquired aplastic anemia was admitted for hematopoietic stem cell transplantation (HSCT) from an ABO and 10/10 HLA compatible 21-year-old sister donor the unmanipulated stem cell product was planned to be infused in 4 h. At the last hour of infusion, the patient had acute hypoxemia, tachycardia, and bilateral pulmonary edema. He was diagnosed with TRALI and completely recovered with supportive therapy in 48 h. The anti-HLA antibody analysis of the donor showed positivity of anti-HLA-DPB1 antibodies. We wanted to emphasize the need for examination of anti-HLA antibodies of the donor and plasma depletion of the product to avoid TRALI in HSCTs from multiparous female donors.